SHOWING EXPLICIT PRESENCE IN ENGLISH RESEARCH ARTICLES: VARIATION ACROSS INDONESIAN AND BRITISH AUTHORS (MENAMPILKAN KEHADIRAN EKSPLISIT DALAM ARTIKEL ILMIAH: VARIASI LINTAS PENULIS INDONESIA DAN INGGRIS) - Adelia Januarto; Tofan Dwi Hardjanto (Metalingua: Jurnal Penelitian Bahasa, 2021)
Unlike previous studies focusing on disciplines and genres displaying regularities in terms of findings, recent studies investigating cultural differences in authorial presence, even in the same language and context suggest contradictory findings, and thus, emphasize the importance of further research to clarify native and non-native English-speaking authors’ variation of showing presence overtly in their texts. Here, we aim at exploring how Indonesian and British authorial presence is linguistically shown in applied linguistics research articles (RAs), and investigating the roles of the linguistic markers of authorial presence in their immediate context. Using data from the two groups of academic authors, we demonstrate that the native English-speaking authors in general tend to be more explicitly visible than their non-native English peers in English RAs and indicate a stronger preference for displaying reader-friendly attitude by showing presence when signposting and providing explicit guidance to their audience.